Mastering Perl for Bioinformatics - James D Tisdall (O'Reilly, 2007)
Bioinformatics is a fast-moving field with problems that require non-trivial programming skills. This text takes the reader from beginner level to the doorstep of advanced material by concentrating on Perl modules and specific applications areas of current and future interest